Еріх Фромм про свободу та її різновиди - Бондаренко, Є. Ю. (ХНУРЕ, 2025)
The work explores the phenomenon of freedom as a fundamental value of human development. Based on the ideas of Erich Fromm, the author analyzes the dual nature of freedom: as an opportunity for self-realization and as a challenge requiring responsibility. Two aspects of freedom are considered: «freedom from» external coercion and «freedom» for creative and educational activities. Special attention is paid to the phenomenon of «escape from freedom», which manifests itself through conformism, authoritarianism and destructiveness. It is emphasized that true freedom provides inner maturity, responsibility and the ability to make conscious choices.
Keywords: Еріх Фромм; різновиди свободи